Conventional Software Testing Using White Box Method - Muhammad Miftakhul Syaikhuddin; Choirul Anam; Ade Rizky Rinaldi; Moch El Bahar Conoras (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
Software development process highly relates to analysis, design, coding, testing and implementation processes. Testing process becomes imperative process to maintain a quality product running well. Testing process can be conducted both for structural and object-oriented software. However, the method utilized for structural and object-oriented software is significantly different. Testing structural program can utilize White Box, Black Box, or Gray testing methods. This study White Box Testing has been employed to test a simple application. The testing process using White Box Testing employs some testing techniques based on path testing consisting of some processes, namely testing independent path, developing flow graph, calculating cyclomatic complexity, and developing graph matrices. Hence, the testing process employing White Box method with basis path testing technique can be executed.